Stakeholder Analysis in the Implementation of Mining Business Licensing Policy in Aceh (Case Study in Krueng Baro Watershed Pidie Regency) - Husna, Nisaul; Idria, Reza; Marzaniar, Putri (Jurnal Ilmiah Ilmu Administrasi Publik, 2025)
This study aims to analyze the actors involved in the implementation of quarry mining business licensing policies, understand their respective roles and interests, and the interactions between actors in influencing policy effectiveness. This study uses a qualitative method with a case study approach, relying on primary data from semi-structured interviews, indirect observation, documentation, and secondary data analysis. The Power-Interest Grid model is used in stakeholder analysis. The results of the study identify thirteen stakeholders involved, dominated by the “subject” type. Most stakeholders have high interests but low power. Two main actors, namely the Aceh Investment and Integrated Services Agency and the Aceh Energy and Mineral Resources Agency, have dominant power in licensing and supervision. The main findings indicate an imbalance of authority between the provincial and district governments, which has led to weak supervision, high risks of environmental damage, and reduced policy implementation effectiveness due to a lack of coordination and low participation of local stakeholders. This study recommends strengthening cross-stakeholder coordination, increasing local stakeholder participation, improving data transparency, and establishing fair, effective, and sustainable policies.